Assessment of Phenotypic Variability in Enset (Ensete Ventricosum (WELW) Cheesman) Accessions Using Multivariate Analysis - Yemataw, Zerihun; Mohamed, Hussien; Yeshitla, Mikias (International Journal of Natural Sciences Research, 2013)
Enset (Ensete ventricosum) is a perennial, banana-like crop, endemic to Ethiopia that produces pseudostem and a starchy belly corm pulped for food, feed and fiber. This study was carried out to ascertain the value and magnitude of genetic diversity among 240 Enset accessions based on their morpho-agronomic traits. A considerable level of polymorphism was observed among Enset accessions for the majority of the morphological characters measured. The accessions were grouped in to five clusters. Cluster and principal component analyses were used to classify Enset accessions on the basis of phenotypic traits. Phenotypically all the cultivars were classified into five major groups. The highest inter-cluster distance (133.95) was observed between clusters II and III.Hence, crossing between accessions included in these clusters may give high heterotic response. The first nine principal components (PCs) with Eigen values greater than one explained 99.98% of the observed variation. Generally, the PC analysis confirmed high diversity of the Enset accessions since the entire variation cannot be explained in terms of few PCs. This in turn, indicates the involvement of the number of traits in contributing towards the overall observed diversity. Regardless of the limitation in estimating total genetic variation, the current study indicated that agro morphological traits were helpful for preliminary characterization and can be used as a broad-spectrum approach to assess genetic diversity among morphologically distinguishable Enset accessions. The distribution of accessions is characterized by high level of endemism which has implications for the conservation of Enset diversity. It is suggested that high land areas owing to the high concentration of diverse and unique landraces there should be given a high priority for collection and in situ germplasm conservation.